Carbon Footprint Assessment of LPG Gas Usage in Small Industries: A Case Study of Sami Laris Swalayan Shopping Center - Aulia Rachma Yuliani; Mega Mutiara Sari; I Wayan Koko Suryawan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
This study aims to assess the carbon footprint associated with the consumption of LPG gas in Sami Laris Swalayan shopping center, focusing on small industries. The research investigates the environmental impact of LPG usage, emphasizing the importance of carbon emissions reduction in the context of sustainable practices. The study quantifies the annual CO2 emissions resulting from LPG gas consumption through data collection and analysis, highlighting the linear relationship between gas usage and carbon emissions. The findings provide valuable insights for the shopping center to develop mitigation strategies and promote sustainable practices for carbon footprint reduction. In addition, the research contributes to the knowledge on carbon emissions in small industries and emphasizes the need for energy-efficient measures and alternative energy sources to minimize environmental impact.